In vitro characterization of the antiviral activity of fucoidan from Cladosiphon okamuranus against Newcastle Disease Virus - Elizondo González, Regina; Cruz Suárez, Lucía Elizabeth; Ricque Marie, Denis; Mendoza Gamboa, Edgar; Rodríguez Padilla, Cristina; Trejo Ávila, Laura M. (BioMed Central Ltd., 2012)
Newcastle Disease Virus (NDV) causes a serious infectious disease in birds that results in severe losses in the worldwide poultry industry. Despite vaccination, NDV outbreaks have increased the necessity of alternative prevention and control measures. Several recent studies focused on antiviral compounds obtained from natural resources. Many extracts from marine organisms have been isolated and tested for pharmacological purposes, and their antiviral activity has been demonstrated in vitro and in vivo. Fucoidan is a sulfated polysaccharide present in the cell wall matrix of brown algae that has been demonstrated to inhibit certain enveloped viruses with low toxicity. This study evaluated the potential antiviral activity and the mechanism of action of fucoidan from Cladosiphon okamuranus against NDV in the Vero cell line